Promotional strategy to convince dial-up users to convert to Streamyx / Nurfaiza Nazura Ramli - Ramli, Nurfaiza Nazura (Faculty of Business and Management, 2008)
Promotional Strategy is very important in determine the successful of the Organizations because of by having good and well planning of Promotional Strategy it will give positive impacts for the organizations. It has been said that, in return to the good promotional strategy, organization can easily to be accepted in the market because customer will aware with the product or services offer by the organizations. The study has been done in conjunction to know the best and effective of "Promotional Strategy to Convince Dial-Up Users to Convert to Streamyx. This is due to high in technology where the dial-up connection is not really suitable because of the speed offered and also the charges of the connection. By conducting the study, researcher will help organization to determine the objective such as what promotional tools that easier to be reach by customer. the benefits gain by Dial-Up Users if they convert to Streamyx and the level of knowledge of the Users related to Streamyx. Lastly, findings and recommendations on the study has been represent and prepare as a guidelines for the organizations or related group in determining the important of having good promotional strategy and help them to have good promotional strategy in future the benefits to the organizations.